Purchasing & supply chain management : analysis, strategy, planning and practice - Weele, A. J. van (Arjan J.) (Andover : Cengage Learning, 2014)
Introducing readers to the key principles underlying purchasing and supply chain management, this text provides them with an in-depth discussion of purchasing and supply issues both from a strategic and managerial perspective.
Includes Internet access.
Previous edition: 2010.
Includes bibliographical references and index.
Keywords: Purchasing -- Management; Business logistics; Achat -- Gestion; Logistique (Organisation); Business logistics; Purchasing -- Management; Ketenbeheer (logistiek); Inkoopbeleid; Voorraadbeheer